Analisis Daya Dukung Lahan Untuk Mendukung Pengembangan Kawasan Berbasis Ekowisata: Studi Kasus di Bukit Surowiti, Gresik, Jawa Timur (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
Indonesia with the very broad span its land, posses a large number of locations that feasible to be develop as a tourism area for supporting the economy of its cities. One of them that potentially to be developed was Bukit Surowiti in Gresik, East Java. Until recently Bukit Surowity only be used as pilgrimage tourism area, with high frequent visitors only happened at certains times of occasion. With the hilly topography condition, the area could offer an alternative type of tourism to be develop. An area itself can be said sustainable if it is supported by the ability to maintain and improve the environmental sustainability as of community economic through direct involvement for tourism development. This study aimed to analyzed the Bukit Surowity physical condition and identified areas that have the most appropriate land-carrying capacity for tourism facilities and supporting infrastructure for its development. The identification was conducted through a field surveys and land characteristics zoning based on the potential of topography, viewing zones and existing vegetation for the need of further analysis and mapping through Visual Absorption Capability method. The result generated a spatial map on the most feasible location for the land development that can become reference for the local government in determine the direction of Bukit Surowiti tourism area development